Prediction structural instability and type attractor of biochemical process - Grytsay, V. I. (Biophysical Bulletin, 2009)
The biochemical process mathematical model of running bioreactor is presented. The scenarios of every regime, which depend on incoming substrate and oxygen flows, are investigated. Points of bifurcation and regularities of forming stable and strange attractors are obtained on a parametric space. The areas diagram of system identical phase-plane portraits is built. A structure functional correspondence of biochemical reactions to the physical properties system is given.